Parents Education Style In Shaping Children's Social Behavior In The School Environment - Rakhma, Ditha (AKADEMIK: Jurnal Mahasiswa Humanis, 2023)
Parents are role models for their children, everything that is attached to them is assessed and used as a reference in the child's daily life, so that starting from the nature, attitude, behavior, and way of thinking the child will have a tendency towards the characteristics of his parents. This becomes very important, how parents consciously provide life education through daily behavior at home, thus forming a good child's personality. In line with this background, this research was conducted to see the style of educating parents towards their children, so that it has an influence on the way children live their lives in the community. In uncovering these objectives, then set a qualitative method with descriptive analysis. This research was conducted on a number of parents in the buffer city of the capital city of Jakarta, as many as 100 people with a simple randomized questionnaire distribution technique. The results of the study explain that the growth and development of children is greatly influenced by the nature, behavior, attitudes and thinking patterns of parents. There is a tendency that is the same or linear, between the behavior of children and their parents. This is inseparable from the way parents educate their children, both formal and informal. Parents with high awareness of educating their children tend to be more motivated to shape their children's attitudes and behavior according to the values ​​and norms that their parents believe to be true. This becomes a learning capital and experience for children to then become part of themselves in living their own lives in society.